VD_FINDINFO HC / 2023 / 781 vom 24. Oktober 2022 - VD Tribunal cantonal (2022)
AVOCAT, POUVOIR DE REPRÉSENTATION, DÉLAI FIXÉ PAR L'AUTORITÉ, INDÉPENDANCE DE L'AVOCAT | 59 al. 1 CPC (CH), 68 al. 2 CPC (CH)